Enhancing Critical Thinking and Mathematical Achievement Through Problem-Based-Learning: A Classroom Action Research at SMKN 6 Surabaya - Sollia Mahani; Puput Wanarti Rusimamto; I Gusto Putu Asto Buditjahjanto; Lilik Anifah (Jurnal Pendidikan Matematika (JPM), 2025)
This study aimed to enhance students’ critical thinking skills and mathematics learning outcomes on the topic of relations and functions through the implementation of the Problem-Based Learning (PBL) model. Conducted as a Classroom Action Research (CAR) at SMKN 6 Surabaya, the study involved 40 students of class X ULP 2 and was carried out over three months in two cycles. Data were collected using tests, observations, and questionnaires. The results showed a significant improvement in cognitive learning outcomes. The average score in the basic cognitive domain (C1–C3) increased from 73.71 in the first cycle to 75.9 in the second cycle. The lowest score rose from 37.5 to 54.2, and the number of students who achieved completion increased from 22 to 34. In the complex cognitive domain (C4–C6) that showed critical thinking skills, the average increased from 40.09 to 61.4. The highest score rose from 70.83 to 91.7, and there were no more students in the low-scoring category. These findings suggest that the PBL approach, when supported by structured assignments and exercises, can effectively foster critical thinking and improve mathematics achievement in vocational high school setting.